2016
DOI: 10.5897/jmpr2015.5985
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and antioxidant activities of Cymbopogon schoenanthus (L.) spreng. essential oil, growing in Illizi - Algeria

Abstract: Hydrodistilled volatile oil obtained from the aerial parts of Cymbopogon schoenanthus cultivated near Illizi, Algeria, was analyzed by Gas Chromatography Mass Spectrometry (GC-MS) and Gas Chromatography -Flame Ionization Detector (GC-FID). More than twenty compounds were identified, representing 94.636% of the total oil. The major constituents of essential oil were piperitone (63.35%), β-eudesmol (9.305%) and elemol (6.915%). Isolated essential oil was tested for radical-scavenging ability using the stable 2,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Other compounds in camel grass include intermedeol (6.1-17.4%), δ-2carene (4.5-10.0%) and elemol (5.2-9.0%) (Pavlovic et al, 2017). Studies on camel grass from Algeria also obtained similar results showing a compound composition of piperitone (63.3%), eudesmol (9.3%), δ-2-carene (4.9%), and elemol (6.9%) (Naima et al, 2016). ) and α-terpineol (6.8-11.7%) (Khadri et al, 2008).…”
Section: Chemical Compounds Of Camel Grassmentioning
confidence: 72%
See 2 more Smart Citations
“…Other compounds in camel grass include intermedeol (6.1-17.4%), δ-2carene (4.5-10.0%) and elemol (5.2-9.0%) (Pavlovic et al, 2017). Studies on camel grass from Algeria also obtained similar results showing a compound composition of piperitone (63.3%), eudesmol (9.3%), δ-2-carene (4.9%), and elemol (6.9%) (Naima et al, 2016). ) and α-terpineol (6.8-11.7%) (Khadri et al, 2008).…”
Section: Chemical Compounds Of Camel Grassmentioning
confidence: 72%
“…and α-terpineol (6.8-11.7%) (Khadri et al, 2008). Hence, this shows that chemical compounds obtained from camel grass can be influenced by geographical conditions, seasons, and time of harvest (Khadri et al, 2008;Ganjewala, 2009;Naima et al, 2016;Pavlovic et al, 2017).…”
Section: Chemical Compounds Of Camel Grassmentioning
confidence: 94%
See 1 more Smart Citation
“…and Rhyzopertha dominica F., two maize seeds pests. Previous investigations in several countries confirm that some plant essential oils not only repel insects but have contact and fumigant insecticidal actions against specific pests, and fungicidal actions against some important plant pathogens (Hellali et al, 2016;Isman, 2000;Sarac and Tunc, 1995). Therefore, essential oils of C. schoenanthus have been shown to present biological effects against Anopheles gambiae and Plutella xylostella at different life stages.…”
Section: Introductionmentioning
confidence: 96%
“…It has quasiubiquitous distribution in Burkina Faso, and even settles in environments apparently less favorable to plants. Like its ubiquitous distribution, the data from literature demonstrated that Cymbopogon species including C. schoenanthus possess various biological properties such as anti-bacterial (Hashim et al, 2017;Hellali et al, 2016), anti-diarrheal, anti-amoebic, anti-filarial, anti-fungal, antiinflammatory, anti-mutagenicity, anti-malarial, antioxidants (Hellali et al, 2016), hypoglycaemic (Dutta et al, 2016), and spasmolytic (Pavlović et al, 2017). Furthermore, studies by different researchers indicate the presence of several chemical groups such as tannins, saponins, saponin glycosides, flavonoids, alkaloids, triterpens, cardiac glycosides, glycosides, steroids and volatile oils in the plant (Pavlović et al, 2017;Amina et al, 2013).…”
Section: Introductionmentioning
confidence: 99%